THE ANALYSIS OF TEACHING WRITING THROUGH GUIDING QUESTIONS - S, Nurhayati (Aksara Public, 2020)
The purposes of this research are to know how guiding questions improve student’s writing skills and to find out the problems when learning writing through the guiding questions. The participants of this research were 19 students of Senior High School; grade X-XII in TPA (Diniyah) Daarul Faiziin in the activity of Community Service on September, 6th, 2020). Classroom Action Research (CAR) was used as the method of the research and the students’ story papers using guiding questions were used as the instruments of the research. The results of the research are: (1) guiding questions with guiding answers helped the learners write a composition (2) some problems were found in teaching writing by categorizing 5 aspects in writiing process : organization, content, vocabulary, grammar and mechanics. The vocabulary and grammar aspects were the dominant problems faced by the learners so that they affected to the results of their composition. It is expected that this study is useful to give some insights to teachers or lecturers of the guiding questions technique in teaching writing.